Restorative Justice as a Solution to the Press Crisis: The Urgency of Reform in the Indonesian Justice System - Nuraeni, Yeni; L. Alfies Sihombing; Komarudin Komarudin (JURNAL USM LAW REVIEW, 2025)
This research aims to explore the potential implementation of restorative justice in the resolution of press offense disputes in Indonesia, with a focus on Law No. 40/1999 on the Press. The urgency of this research arises from the need to reduce the burden on the increasingly heavy judicial system and increase the effectiveness of media dispute resolution. In this context, restorative justice can be a more humane and efficient alternative to conventional litigation approaches. The scope of the problem includes the lack of regulations supporting restorative mechanisms in the Press Law, as well as practical challenges in implementing mediation in Indonesia. The main findings show that restorative justice can help restore social relations between the parties involved, in a more constructive way, rather than simply imposing punishment. The novelty of this research lies in identifying the potential application of restorative justice in the context of press disputes, as well as the role of the Press Council as a mediator in dispute resolution mechanisms. The method used in this research is legal analysis and comparison of legal systems in other countries, as well as a study of restorative justice theory and its application in press disputes in Indonesia.